Redefining Death in Zero K by Don DeLillo - Jagła, Agnieszka (Text Matters: A Journal of Literature, Theory and Culture, 2025)
Don DeLillo’s Zero K (2016) focuses on the possibility of overcoming death through cryonics. The narrative is set primarily in the Convergence—a facility which utilises cryonics to provide its subjects with the possibility of life extension, and a promise of a better life in the future. The result is achieved by removing the subjects’ internal organs and keeping them alive in a state of life suspension, in an attempt to renegotiate the limits of human existence. As his father and stepmother become patients of the Convergence, the protagonist of the novel, Jeff Lockhart, grapples with the questions of life and death. The paper analyses the theme of death in the novel from the posthumanist perspective of Rosi Braidotti’s text “The Ethics of Becoming Imperceptible,” and compares it with the pursuit of immortality highlighted by the transhumanist movement. The secondary purpose of this paper is to investigate how the novel redefines grief by using the framework provided by Monika Rogowska-Stangret’s ethical stance presented in Być ze świata (Being-of-the-World).